Economic Development and Multilateral Trade Cooperation - Evenett, Simon J. (Washington, DC: World Bank and Palgrave Macmillan, 2012)
How can international trade agreements promote development and how can rules be designed to benefit poor countries? Can multilateral trade cooperation in the World Trade Organization (WTO) help developing countries create and strengthen institutions and regulatory regimes that will enhance the gains from trade and integration into the global economy? And should this even be done? These are questions that confront policy makers and citizens in both rich and poor countries, and they are the subject of this publication. It analyzes how the trading system could be made more supportive of economic development, without eroding the core WTO functions.